2003
DOI: 10.1046/j.1365-2818.2003.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐localization analysis of complex formation among membrane proteins by computerized fluorescence microscopy: application to immunofluorescence co‐patching studies

Abstract: SummaryFluorescence imaging of two independently labelled proteins is commonly used to determine their co-localization in cells. Antibody-mediated crosslinking can mediate the patching of such proteins at the cell surface, and their co-localization can serve to determine complex formation among them. However, manual analysis of such studies is both tedious and subjective. Here we present a digital co-localization analysis that is independent of the fluorescence intensity, is highly consistent and reproducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 30 publications
3
130
0
Order By: Relevance
“…Fluorescence digital images were recorded using a CCD camera (CoolSnap HQ, Photometrics) coupled to an Axioimager D.1 fluorescence microscope (Carl Zeiss Microimaging) with a 100ϫ/1.4 NA oil-immersion objective as described (39). The Alexa 488 (green) and Alexa 594 (red) TIFF images were exported to Image-Pro Plus (Media Cybernetics, Bethesda, MD) and subjected to quantitative analysis of the extent of copatching using an algorithm we have recently developed (39).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence digital images were recorded using a CCD camera (CoolSnap HQ, Photometrics) coupled to an Axioimager D.1 fluorescence microscope (Carl Zeiss Microimaging) with a 100ϫ/1.4 NA oil-immersion objective as described (39). The Alexa 488 (green) and Alexa 594 (red) TIFF images were exported to Image-Pro Plus (Media Cybernetics, Bethesda, MD) and subjected to quantitative analysis of the extent of copatching using an algorithm we have recently developed (39).…”
Section: Methodsmentioning
confidence: 99%
“…The Alexa 488 (green) and Alexa 594 (red) TIFF images were exported to Image-Pro Plus (Media Cybernetics, Bethesda, MD) and subjected to quantitative analysis of the extent of copatching using an algorithm we have recently developed (39). Briefly, the program segments the patches in a user-defined region of interest, subtracts the background, and identifies the center of mass of each object in the green and red images.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we used antibody cross-linking of extracellularly FLAG-tagged MAL (MAL-FLAG) with primary anti-FLAG and secondary Cy3-modified anti-mouse antibodies (Figure 3d) (Lachmanovich et al, 2003). We found that similar to DiHcRED-MAL OCs, crosslinking of MAL-FLAG mediated by divalent antibodies results in a local increase in the concentrations of GPI-FP and GM1.…”
Section: Characterization Of Dihcred-mal Clustersmentioning
confidence: 99%
“…Sequential frame acquisition was used to eliminate cross-talk between the two fluorescence channels. Colocalization was characterized using the method of Lachmanovich et al (2003). Briefly, the peaks were segmented using a local threshold set at half the maximum value of the local peak.…”
Section: Immunofluorescence Analysismentioning
confidence: 99%